Contribution of advanced edge detection filters for the structural mapping of the Douala Sedimentary Basin along the Gulf of Guinea - Gautier Kamto, Paul; Oksum, Erdinc; Pham Luan, Thanh; Kamguia, Joseph (Vietnam Journal of Earth Sciences, 2023)
The Douala sedimentary basin (DSB) is an area of interest because of its hydrocarbon potential. Geophysical investigations in this basin are necessary to understand its structural features better. In this study, we aimed to highlight the major lineaments of the DSB by interpreting gravity data using advanced edge detection filters based on various combinations of the horizontal and vertical gradients of the field, namely the total horizontal gradient (THG), analytical signal (AS), theta map (TM), gradient amplitude of the vertical derivative (THG_VD), the tilt angle of the total horizontal gradient amplitude (TAHG) and a novel edge detector based on the soft sign function (SF). These filters were first tested on synthetic data of a simple density model to examine their effectiveness. The results show that the edges of the model structures can be visualized with greater accuracy using the TAHG and SF filters compared to the results from the others. Further, although the TAHG and SF filters produced good results in identifying shallow and deep structures, solutions from SF proved to be better at delineating edges. Next, we applied these edge detection filters to the residual gravity anomaly of the study area obtained after a filtering process on the complete Bouguer anomaly. The SF filter clearly and accurately identifies the major structural features. The existence and location of previously unidentified lineaments have been shown. Most of the lineaments of the DSB extracted by this study provide geometric information on the lateral distribution of depositional successions filling the basin. The structural features are mainly concentrically from the volcanic center of Mount Cameroon and show that the DSB has probably been affected by earthquakes from the permanent activities of the Cameroon volcanic line since the Cretaceous. The highlighted lineaments of the DSB obtained from this study may shed light on future studies to improve mineral/hydrocarbon exploitation and update the area’s geological/tectonic information.